MKG Collection Online: The potential of open museum collections - Schmidt, Antje (Hamburger Journal für Kulturanthropologie (HJK), 2018)
In October 2015 the Museum für Kunst und Gewerbe Hamburg (MKG) launched the “MKG Collection Online”. The MKG is the first art museum in the German-speaking countries to open up its collections by establishing an open access policy. It offers digital images of objects that are already in the public domain and data of all of the published objects for unrestricted reuse in order to inspire creative processes, foster knowledge production and innovation and safeguard cultural heritage. Many museums are, however, struggling with this concept, even though it is recommended as best practice by the European Commission. Looking at the example of the MKG, the potential of open access for digitized museum collections will be outlined. Furthermore, the challenges of this open access policy and the wider implications of openness for the museum, other cultural heritage institutions and society will be discussed.